Email us to get an instant 20% discount on highly effective K-12 Math & English kwizNET Programs!

#### Online Quiz (WorksheetABCD)

Questions Per Quiz = 2 4 6 8 10

### High School Mathematics5.6 Revision of Algebraic Expressions - VI

 Examples: Expand, (x + 2y + 3z)(x2 + 4y2 + 9z2 - 2xy - 6yz - 3xz). Given that, (x + 2y + 3z)(x2 + 4y2 + 9z2 - 2xy - 6yz - 3xz), This is in the form of, (a + b + c)(a2 + b2 + c2 - ab - bc - ca) = a3 + b3 + c3 - 3abc. Here a = x, b = 2y and c = 3z. = (x)3 + (2y)3 + (3z)3 - 3.x.2y.3z = x3 + 8y3 + 27z3 - 18xyz Expand, (7x + 3)(4x+2). Given that, (7x + 3)(4x+2). This is in the form of (ax + b)(cx + d) = (ac)x2 + (ad + bc)x + bd Here a = 7, b = 3, c = 4 and d = 2. = (7 * 4)x2 + (7*2 + 4*3)x + 6 = 28x2 + 26x + 6 Expand, (x+3)(x+2)(x+1). Given that, (x+3)(x+2)(x+1). Formula for this is , (x+a)(x+b)(x+c) = x3 + (a+b+c)x2 + (ab + bc + ca)x + abc Here, a = 3, b = 2 and c = 1 = x3 + (a+b+c)x2 + (6+2+3)x + 3.2.1 = x3 + 6x2 + 11x + 6 Directions: Solve the following problems. Also write at least 10 examples of your own.
 Q 1: Expand, (2x + y + z)(4x2 + y2 + z2 - 4xy - yz - 2xz).8x3 + y3 + z3 - 6xyz8x3 + y3 + z3 - 6xyz4x3 + y3 + z3 - 3xyz Question 2: This question is available to subscribers only!